Association of body composition with survival and inflammatory responses in patients with non-metastatic nasopharyngeal cancer. (September 2020) - He, Wen-Zhuo; Jiang, Chang; Liu, Li-Li; Yin, Chen-Xi; Rong, Yu-Ming; Hu, Wan-Ming; Yang, Lin; Wang, Lei; Jin, Ya-Nan; Lin, Xiao-Ping; Liu, Shou-Sheng; Huang, Jin-Sheng; et al.
Highlights: Low VAT and SAT were both associated with worse survival in patients with NPC. The prognostic value of VAT was independent of other well-known prognostic factors. IMAT and sarcopenia were not with prognostic value in patients with NPC. Abstract: Objectives: It is unknown whether or not the body composition is correlated with the prognosis and inflammatory response in patients with nasopharyngeal cancer (NPC). Materials and methods: This cohort included 1767 patients with NPC. Visceral, subcutaneous and intra muscular adipose tissues (VAT, SAT and IMAT), and skeletal muscle index were quantified with computed tomography. We used the optimal stratification to select cut points for VAT, SAT and IMAT. We defined sarcopenia according to a widely used cut-point. The primary endpoint was overall survival (OS). The association between body composition and inflammatory response was also examined. Results: Low VAT, SAT, IMAT and sarcopenia were observed in 260 (14.7%), 451 (25.5%), 773 (43.7%) and 683 (38.7%) patients, respectively. Low VAT ( P  < 0.001, hazard ratio [HR], 1.884; 95% confidence interval [CI], 1.436–2.473, ) and SAT ( P  = 0.022, HR, 1.334, 95%CI, 1.043–1.706) were both associated worse survival. IMAT and sarcopenia were not with prognostic value. In multivariate analysis, we found the prognostic value of the VAT (HR: 1.544, 95% CI: 1.128–2.114; P  = 0.007) was independent of T stage, N stage, disease stage, lactic dehydrogenase, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), the systemic immune-inflammation index (SII), EBV-DNA and body mass index. We observed higher NLR ( P  = 0.028) and PLR ( P  < 0.001) in patients with low SAT. Both low VAT ( P  = 0.009) and SAT ( P  = 0.005) were associated with decreased stromal lymphocyte infiltrating intensity. Conclusions: Among body composition parameters, VAT was an independent prognostic factor, especially in patients with locally advanced NPC.